“A READER, NOT A SPEAKER”: ON THE VERBAL, PARAVERBAL AND NONVERBAL COMMUNICATION TRICHOTOMY - Ridao, Susana (2017)
This paper aims to analyze the relevance of verbal, paraverbal and nonverbal communication for a group of students by observing and evaluating a speaker’s speech. The corpus analyzed is composed of the notes made by 30 students about the communicative flaws detected in a speaker’s speech. The results obtained indicate that 11.27% of such criticisms were aimed at verbal communication, 30.82% at paraverbal communication and 57.89% at nonverbal communication. Therefore, these conclusions are similar to those reached by Mehrabian (1972), although they differ in part from the ones presented in van der Hofstadt (2005) or Orzáiz (2009). The implications of these results are discussed.